Rekayasa Sistem Integrasi Keilmuan Berdasarkan Bentuk Interkonektif-Integratif - Syahbudin (Jurnal INSYPRO (Information System and Processing), 2022)
This study focuses on efforts to find methods of grouping data, labeling knowledge, extracting techniques and building a scientific integration system design within the scope of Islamic universities. This study uses a qualitative method by evaluating various aspects. These aspects include data collection technology, data labeling techniques, as well as exploring scientific integration. Sources of data in this study are the subject of each teaching material and reference books in each course. Recognizing this difference, the data sources are stored in different storage. Storage media with related databases implemented to store the subject matter while teaching materials are stored in separate folders from the database system. When labeling is done on a structured database with label rules referring to the knowledge management approach. This intended to support the selection of appropriate knowledge mining methods. While the text mining method will be applied to document-based storage. The result of this research is the design of a scientific integration system that can be implementation and discovery of scientific integration patterns between courses and between study programs.